If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4x+2x=9-10
We move all terms to the left:
-4x+2x-(9-10)=0
We add all the numbers together, and all the variables
-4x+2x-(-1)=0
We add all the numbers together, and all the variables
-2x+1=0
We move all terms containing x to the left, all other terms to the right
-2x=-1
x=-1/-2
x=1/2
| 3(x-2)^2-8=40 | | 9t(2t-4)=25 | | 8x-2x=11+9 | | F(x)=90(1.36) | | 4y=-16/3 | | 10/p=7/9 | | 4b-8b=-4 | | -3.5=k2.8 | | 8x+31.45=55.45 | | 5x-2=6x-18 | | 3x-5+2x-15=x | | 1/6(2x+42)=1/4x-2 | | 8j+j=18 | | 20x+.50=35 | | 16^7a+8=38 | | n/14=-10/7 | | Y=40.x | | p=0.25p | | 4z−2z+–3z=5 | | (-0.1x)=-6 | | 3w^2+15w+12=w | | −4x+24=2x+12 | | -10=11y+12 | | a^-2.25a=0 | | 16.19+z=27 | | 4y+8=2y+12 | | 10=12p | | 700=29p | | 6+2n,n=-4 | | x/3-8=(20) | | -48=x5/8 | | 60w=3/4*100 |